Macroeconomic and monetary policy-making at the European Commission, from the Rome Treaties to the Hague Summit - Ivo Maes (National Bank of Belgium, 2004)
This paper discusses macroeconomic and monetary policy-making at the European Commission, covering the period from the Rome Treaties to the Hague Summit. It is based on an analysis of public documents, archival research and interviews with former policy-makers. The paper starts with an overview of the economic philosophy of the Rome Treaties and senior macroeconomic policy-makers at the Commission, followed by an analysis of economic developments in the 1960s. Thereafter, the focus is on three crucial macroeconomic policy documents of the period: the European Reserve Fund project in 1958, the Commission's Action Programme for the Second Stage of the EEC of October 1962 and the Barre Memorandum of October 1969. The Commission's objectives tended to be both defensive, preserving the "acquis communautaire", especially avoiding recourse to the safeguard clauses, and pro-active, stimulating the process of European integration. From an analytical point of view, the Commission focussed on the compatibility of policies between the Member States. Gradually, a typical Commission analysis developed, based on a blending of German convergence ideas with the French medium-term approach. The paper further illustrates the ascent of the Commission as an actor in the monetary area, notwithstanding the relatively limited provisions of the EEC Treaty.
Keywords: A11; B20; E60; F02; N14; P16; 330; macroeconomic and monetary policy-making; European Commission; Rome Treaty; European Reserve Fund; Action Programme for the Second Stage; Barre Memorandum; the Hague Summit; Eurozone; Wirtschaftspolitik; Ökonomische Ideengeschichte; EU-Staaten